2016
DOI: 10.18632/oncotarget.10288
|View full text |Cite
|
Sign up to set email alerts
|

IL-8, GRO and MCP-1 produced by hepatocellular carcinoma microenvironment determine the migratory capacity of human bone marrow-derived mesenchymal stromal cells without affecting tumor aggressiveness

Abstract: New therapies are needed for advanced hepatocellular carcinoma (HCC) and the use of mesenchymal stromal cells (MSCs) carrying therapeutic genes is a promising strategy. HCC produce cytokines recruiting MSCs to the tumor milieu and modifying its biological properties. Our aim was to study changes generated on human MSCs exposed to conditioned media (CM) derived from human HCC fresh samples and xenografts. All CM shared similar cytokines expression pattern including CXCL1-2-3/GRO, CCL2/MCP-1 and CXCL8/IL-8 being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
(35 reference statements)
0
27
0
Order By: Relevance
“…MSCs can be used to suppress the development of HCC. Their multipotency, immunoregulatory, pro-regenerative effects (Hsu et al, 2017) and their chemotactic properties to home to tumor invaded regions make them a good candidate for cancer therapy (Bayo et al, 2017). MSCs inhibit tumor growth by increasing inflammatory infiltration (Ohlsson et al, 2003), inhibiting angiogenesis (Otsu et al, 2009), suppressing the signaling of Wnt (Qiao et al, 2008a;Qiao et al, 2008b) and AKT (Khakoo et al, 2006), and inducing cell cycle arrest and apoptosis 4 (Cousin et al, 2009;Dasari et al, 2010;Lu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can be used to suppress the development of HCC. Their multipotency, immunoregulatory, pro-regenerative effects (Hsu et al, 2017) and their chemotactic properties to home to tumor invaded regions make them a good candidate for cancer therapy (Bayo et al, 2017). MSCs inhibit tumor growth by increasing inflammatory infiltration (Ohlsson et al, 2003), inhibiting angiogenesis (Otsu et al, 2009), suppressing the signaling of Wnt (Qiao et al, 2008a;Qiao et al, 2008b) and AKT (Khakoo et al, 2006), and inducing cell cycle arrest and apoptosis 4 (Cousin et al, 2009;Dasari et al, 2010;Lu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The first reports indicated that MSCs inhibited HCC growth in vitro and in vivo (75,76). However, other results demonstrated either a pro-tumorigenic effect (77,78) or a null effect of MSCs on HCC growth (35,36,(79)(80)(81)(82). The inhibition of tumor growth was associated with Wnt, NF-κB, and PI3-K/Akt signaling pathways (75,83), whereas enhancement of microvessel density was observed in the case of tumor progression (77,78).…”
Section: The Tumor Microenvironment In Hcc Progression and Metastasismentioning
confidence: 99%
“…Consequently, MSCs can be recruited to these tumor sites and activated to have repair and immunomodulation functions. Several factors such as interleukin (IL)-8, monocyte chemoattractant protein-1, growth-regulated oncogene, and autocrine motility factor, produced by the HCC, are known to attract and recruit MSCs (35,36). It is known that MSCs can secrete several growth factors, cytokines, chemokines, and ECM components (37).…”
Section: Cellular Componentsmentioning
confidence: 99%
“…When liver tissue or cells stimulate with stimulants like alcohol and fatty acid, liver tissue synthesizes various types of cytokines to defend that [20][21][22][23][24][25] . The well-studied cytokines include tumor necrosis factor-α (TNF-α) [26,27] , interleukin family (IL-6, IL-1β) [7,28,29] , chemokines (VCAM-1, ICAM-1 and MCP-1) [30][31][32][33] , etc. TNF-α and IL-6 are two multifunctional cytokines in chronic hepatic inflammation.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%